The Role of Islamic Religious Education in Shaping Student Character in the Digital Era - M. Hasyim Asy’ari (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This research aims to analyze the role of Islamic religious education in shaping the character of students in the digital era through aliterature review. The digital era has brought significant changes in the thinking patterns, behavior and social interactions of the younger generation. In this context, Islamic religious education has a strategic role in instilling strong moral and ethical values. Through a literature review that includes the latest research, this article explores how Islamic religious education can contribute to the formation of good character and be adaptive to technological developments. Research findings show that theintegration of Islamic religious education with digital technology can increase the effectiveness of learning and strengthen the character of students, so that they are able to face the challenges and dynamics of life in the modern era.